The effect of inosine supplementation on aerobic and anaerobic cycling performance - Starling, R. D.; Trappe, T. A.; Short, K. R.; Sheffield-Moore, M.; Jozsi, A. C.; Fink, W. J.; Costill, D. L. (Medicine & Science in Sports & Exercise, 1996)
[Inosine is not an amino acid but is classified as a nucleoside. It is associated with the development of purines, nonprotein nitrogen compounds that have important roles in energy metabolism. It has been suggested that inosine may improve ATP production in the muscle and thus be of value to strength athletes. It is also thought to enhance oxygen delivery to the muscles which would benefit endurance athletes. There are no data to support these claims.] Male competitive cyclists (N = 10) completed a Wingate Bike Test, a 30-min self-paced endurance cycling performance, and a constant load supramaximal sprint test to fatigue following five days of oral supplementation (5,000 mg/day) with inosine and a placebo. It was found that inosine supplementation did not improve endurance or power (sprint) performance. It was observed that under some conditions, inosine supplementation might even be detrimental to performance. Implication. Inosine supplementation does not appear to have beneficial effects on endurance or sprint performance.